please i want full solution of this quesrion
Attachments:
![](https://hi-static.z-dn.net/files/d82/c23838aa2f2152d68c5bcd79039fdb5c.jpg)
Answers
Answered by
0
Answer:
firstly rationalise the denominator and then squre them according to the question
Answered by
1
hey ❗❗
given here
x= (√3+√2)/(√3-√2)
y= (√3-√2)/(√3+√2)
find here
x²+y²=?
Solution :-
x=(√3+√2)/(√3-√2)
x=(√3+√2)(√3+√2)/(√3+√2)(√3-√2)
x= (3+2+2√6)/(3-2)
x= 5+2√6
so,
x²= (5+2√6)²
=25+24+20√6
=49+20√6
and
y= (√3-√2)/(√3+√2)
y= (√3-√2)(√3-√2)/(√3+√2)(√3-√2)
y= (3+2-2√6)/(3-2)
y= 5-2√6
y²= (5-2√6)²
=25+24-20√6
= 49-20√6
so,
x²-y²
= (49+20√6)-(49-20√6)
= 49+20√6-49+20√6
=40√6
I hopes its help's u
Follow me..✌✌
@Abhi.❤❤
Similar questions